The effects of virgin coconut oil on fibroblasts and myofibroblasts on diabetic wound healing - Wong, SK; Rangiah T,; Bakri NSA,; Ismail WNA,; Bojeng EEF,; Abd Rahiman MA,; Soliman AM,; Ghafar N,; Das S,; Teoh, Seong Lin (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Delayed wound healing is one of the major complications of diabetes mellitus where it often leads to amputation. Virgin coconut oil (VCO) is a natural oil widely used to treat wounds and burns traditionally. It possesses potent antioxidant and antibacterial activities. This study aimed to determine the effect of VCO on the fibroblast population in diabetic wound healing. Full thickness cutaneous wound tissues were collected from non-treated, VCO-treated, and silver sulfadiazine (SS)- treated diabetic rats. The tissues were then subjected to Verhoeff eosin staining and immunohistology of fibroblast and myofibroblast. Histological analysis showed increased collagen deposition with intact epidermis in the VCO treated group compared to decreased collagen deposition with damaged epidermis in both nontreated and SS-treated groups. Interestingly, more fibroblasts and myofibroblasts were observed in the non-treated group compared to the VCO- and SS-treated groups. VCO significantly promoted wound healing process in diabetic rats via promoting re-epithelialization, and increasing collagen fibres deposition and wound contraction. The results suggested VCO can be used to treat diabetic wounds.